Auxiliar de ingeniería en dirección mantenimiento y proyectos (2022)
This report supports the activities that were carried out during the internship at the company Acerías Paz del Río. The activities that were carried out fit the professional profile of a civil engineer. The internship lasted 6 months from December 14, 2021 to June 14, 2022 at the Belencito-Boyacá headquarters. The internship focused on the support of the civil works group in the project area, focusing on the follow-up and supervision of works, the completion of formats such as technical sheets, layout, company budget tables, among others. During the internship different professional and academic challenges arose. A project assistant at the Acerías Paz del Rio company had to be a skilled person, a leader Civil Engineering, being one of the professions with the most work fields, gave me the opportunity to do my internship at the Acerías Paz del Rio company, being an assistant in engineering in maintenance and project management, having as main functions the support in the preparation of technical sheets, the survey of quantities on site, the support in the preparation of budgets, the support in enforcing established schedules, support to the auditing in general .